Functional Versus Anatomic Assessment of Myocardial Bridging by Intravascular Ultrasound: Impact of Arterial Compression on Proximal Atherosclerotic Plaque. Issue 4 (April 2016) - Yamada, Ryotaro; Tremmel, Jennifer A.; Tanaka, Shigemitsu; Lin, Shin; Kobayashi, Yuhei; Hollak, M. Brooke; Yock, Paul G.; Fitzgerald, Peter J.; Schnittger, Ingela; Honda, Yasuhiro
Abstract : Background: The presence of a myocardial bridge (MB) has been shown to promote atherosclerotic plaque formation proximal to the MB, presumably because of hemodynamic disturbances provoked by retrograde blood flow toward this segment in cardiac systole. We aimed to determine the anatomic and functional properties of an MB related to the extent of atherosclerosis assessed by intravascular ultrasound. Methods and Results: We enrolled 100 patients with angina but no significant obstructive coronary artery disease who had an intravascular ultrasound–detected MB in the left anterior descending artery (median age 54 years, 36% male). The MB was identified with intravascular ultrasound by the presence of an echolucent band (halo). Anatomically, the MB length was 22±13 mm, and halo thickness was 0.7±0.6 mm. Functionally, systolic arterial compression was 23±12%. The maximum plaque burden up to 20 mm proximal to the MB entrance was significantly greater than the maximum plaque burden within the MB segment. Among the intravascular ultrasound–defined MB properties, arterial compression was the sole MB parameter that demonstrated a significant positive correlation with maximum plaque burden up to 20 mm proximal to the MB entrance ( r =0.254, P =0.011 overall; r =0.545, P <0.001 low coronary risk). In multivariate analysis, adjusting for clinical characteristics and coronary risk factors, arterial compression was independently associated with maximum plaque burden up to 20 mm proximal to the MB entrance. Conclusions: In patients with an MB in the left anterior descending artery, the percentage of arterial compression is related directly to the burden of atherosclerotic plaque located proximally to the MB, particularly in patients who otherwise have low coronary risk. This may prove helpful in identifying high‐risk MB patients.